Concurrent Isosporiasis and Toxocariasis in a Persian Kitten: Clinical Diagnosis and Therapeutic Management - Syarifuddin, Ahmad; Safitri, Jessica Anggun; Rizky , Asri; Damhuri, Dedi (Universitas Airlangga, 2025)
Background: Isosporiasis, caused by Isospora spp., is a common intestinal parasitic infection in kittens, transmitted via ingestion of oocysts in contaminated food, water, or feces. Concurrent infections with nematodes such as Toxocara spp. can complicate clinical management. Purpose: To provide clinical insights into the diagnosis and management of simultaneous isosporiasis and toxocariasis in kittens. Case(s): A 1-month-old, 0.7 kg female Persian kitten named Alin was presented with pasty diarrhea. The kitten had good appetite and hydration, with no prior deworming or vaccination. Clinical examination revealed respiratory rate 104 breaths/min, pulse 156 beats/min, and rectal temperature 39.9°C. Abdominal palpation showed distension and auscultation revealed hyperactive intestinal sounds. Fecal analysis detected Isospora spp., oocysts and Toxocara spp. eggs, confirming co-infection. Case Management: Initial treatment included oral Cotrimoxazole and CTM powder for isosporiasis and Pyrantel Pamoate (Chombantrine®) for toxocariasis, administered three times daily for five days. Persistent infection on follow-up prompted four additional days of CTM therapy. By November 6, 2024, Isospora spp., remained detectable; CTM was discontinued, deworming repeated, and intramuscular Intertim LA was administered for maintenance therapy. Conclusion: Simultaneous isosporiasis and toxocariasis may require extended combined therapy due to potential resistance of Isospora spp. Routine deworming, strict hygiene, and early diagnostic monitoring are essential to prevent and manage such infections in kittens.